Fatal Pneumonia Associated With a Novel Genotype of Human Coronavirus OC43 - Lau, Susanna Kar Pui; Li, Kenneth Sze Ming; Li, Xin; Tsang, Ka-Yan; Sridhar, Siddharth; Woo, Patrick Chiu Yat (Frontiers in Microbiology, 2022)
Since its first discovery in 1967, human coronavirus OC43 (HCoV-OC43) has been associated with mild self-limiting upper respiratory infections worldwide. Fatal primary pneumonia due to HCoV-OC43 is not frequently described. This study describes a case of fatal primary pneumonia associated with HCoV-OC43 in a 75-year-old patient with good past health. The viral loads of the respiratory tract specimens (bronchoalveolar lavage and endotracheal aspirate) from diagnosis to death were persistently high (3.49 × 106–1.10 × 1010 copies/ml). HCoV-OC43 at a 6.46 × 103 copies/ml level was also detected from his pleural fluid 2 days before his death. Complete genome sequencing and phylogenetic analysis showed that the present HCoV-OC43 forms a distinct cluster with three other HCoV-OC43 from United States, with a bootstrap value of 100% and sharing 99.9% nucleotide identities. Pairwise genetic distance between this cluster and other HCoV-OC43 genotypes ranged from 0.27 ± 0.02% to 1.25 ± 0.01%. In contrast, the lowest pairwise genetic distance between existing HCoV-OC43 genotypes was 0.26 ± 0.02%, suggesting that this cluster constitutes a novel HCoV-OC43 genotype, which we named genotype I. Unlike genotypes D, E, F, G, and H, no recombination event was observed for this novel genotype. Structural modeling revealed that the loop with the S1/S2 cleavage site was four amino acids longer than other HCoV-OC43, making it more exposed and accessible to protease, which may have resulted in its possible hypervirulence.